Optimalisasi Penggunaan Masker pada Anak di Era Pandemi Covid-19 melalui Metode Storytelling di TK Mawar Gambut - Chandra Chandra; Meilya Farika Indah; Eddy Rahman; Ahmad Zacky Anwary; Asrinawaty Asrinawaty; Zuhrupal Hadi; Norsita Agustina (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Kindergarten (TK) education is an early stage of education as children who are experiencing a developmental transition really need an approach that can overcome the problems experienced, one of which is implementing the COVID-19 pandemic health protocol such as the use of good and correct masks. The purpose of this activity is to help improve social skills such as communication skills, through community service, community empowerment programs at Mawar Kindergarten, Gambut District through storytelling with a focus on doing fairy tales to children in order to be able to respond to the use of masks properly and correctly. The method of this activity is a fairy tale through storytelling to students with the title